Strengthening capacity to improve nutrition - Gillespie, Stuart (International Food Policy Research Institute, 2001)
A major premise of this paper is that the failure—or limited achievements—of many large-scale nutrition programs is very often a function of insufficient sustainable capacities within communities and organizations responsible for implementing them. Following a brief review of the various rationales for an intensified focus on capacity and capacity development, the paper examines the linkages between nutrition programming and capacity development processes before proposing a new approach to assessing, analyzing, and developing capacity. The ensuing sections then focus in more detail on the ingredients and influences of capacity at the levels of the community, program management, supporting institutions, and the government. Finally, the implications of a more proactive focus on strengthening nutrition capacity for donor modes of operation and support priorities are discussed.